Aluminum-Based Heterogeneous Surface for Efficient Solar Desalination and Fog Harvesting Processed by a Picosecond Laser - Liang, Zihang; Wang, Qingwei; Chu, Dongkai; Naqvi, M. Jahanzaib; Qu, Shuoshuo; Huang, Jun; Yao, Peng (ACS applied materials & interfaces, 2023)
Solar desalination and fog harvesting are two common ways to obtain fresh water, and both are promising methods to solve the water shortage problem. However, through either the fabrication of interfacial evaporators for solar desalination or the preparation of superwetting surfaces for fog harvesting, current methods suffer from long preparation times, high costs, and low efficiency. Herein, we report an efficient and simple method to process heterogeneous surfaces (HSs) on aluminum (Al) by picosecond laser processing combined with chemical treatment used for fog harvesting and seawater desalination. The as-prepared HS simultaneously consists of regular periodic stripe structures with superhydrophilicity and superhydrophobicity. The spacing of the superhydrophilic and superhydrophobic regions can be adjusted through the processing path. This surface has a 44% improvement in fog harvesting efficiency compared to a pristine Al sheet, which is 0.53 kg·m–2·h–1. Furthermore, it shows a high evaporation rate of 2.35 kg·m–2·h–1 under one sun irradiation with an energy efficiency of 52.39%. Such functional surfaces can be applied to obtain fresh water resources in both coastal regions and arid areas, where water mist is relatively abundant, providing reference and guidance for fresh water collection, and being a promising way to solve the water shortage problem.